Corporate governance and banks: What have we learned from the financial crisis? : Hamid Mehran; Alan Morrison; Joel Shapiro - Hamid Mehran; Alan Morrison; Joel Shapiro (Federal Reserve Bank of New York, 2011)
Recent academic work and policy analysis give insight into the governance problems exposed by the financial crisis and suggest possible solutions. We begin this paper by explaining why governance of banks differs from governance of nonfinancial firms. We then look at four areas of governance: executive compensation, boards, risk management, and market discipline. We discuss promising solutions and areas where further research is needed.
Keywords: G01; G21; G32; G39; 330; governance; banks; Corporate Governance; Bank; Finanzmarktkrise